Breast Painful Swelling at Breast Tail in Lactating Lady in Her Fourth Birth: A Rare Case of Sudden Accessory Breast Tissue with Intraoperative Finding of Significant Milk - Reem Alsalamah (International Journal of Biomedicine)
Accessory breast tissue is an uncommon condition that affects 2%-6% of women, a third of whom have more than one area of supernumerary tissue growth. We present a case of accessory breast tissue in a 34-year-old woman with a month-long history of bilateral chest pain associated with a bilateral breast tail mass. She has four children; the youngest is six months old and breastfeeding. The patient underwent excision of both masses. Intraoperatively, we found that the area of concern showed breast tissue full of a large amount of milk, which explained her symptoms. The patient underwent the intervention with no intra or postoperative complications. After a two-year follow-up, the patient is doing fine with no concern; radiologically, there is no residual breast tissue in the area of concern.